2008
DOI: 10.1063/1.2965797
|View full text |Cite
|
Sign up to set email alerts
|

Laser action in nanowires: Observation of the transition from amplified spontaneous emission to laser oscillation

Abstract: Direct evidence of the transition from amplified spontaneous emission to laser action in optically pumped zinc oxide (ZnO) nanowires, at room temperature, is presented. The optical power evolves from a superlinear to a linear regime as the pump power exceeds threshold, concomitant with a transition to directional emission along the nanowire and the emergence of well defined cavity Fabry–Pérot modes around a wavelength of ≈385 nm, the intensity of which exceeds the spontaneous emission background by orders of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

12
209
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 243 publications
(221 citation statements)
references
References 13 publications
12
209
0
Order By: Relevance
“…mode spacing) for a Fabry-Perot cavity is given by Δλ = λ 2 [2L(nλdn/dλ)] -1 . Using reported values for n (2.4) and dn/dλ (-0.015 nm -1 ) at λ = 387 nm, 11 and L = 8.1 μm determined by SEM imaging, Δλ is calculated at 1.53 nm, which agrees well with the experimentally observed mode spacings of 1.6 nm. The observed redshift in lasing modes at higher excitation pump energies is a result of bandgap renormalization with the semiconductor nanowire, which causes longer wavelengths to be preferentially amplified.…”
supporting
confidence: 82%
See 1 more Smart Citation
“…mode spacing) for a Fabry-Perot cavity is given by Δλ = λ 2 [2L(nλdn/dλ)] -1 . Using reported values for n (2.4) and dn/dλ (-0.015 nm -1 ) at λ = 387 nm, 11 and L = 8.1 μm determined by SEM imaging, Δλ is calculated at 1.53 nm, which agrees well with the experimentally observed mode spacings of 1.6 nm. The observed redshift in lasing modes at higher excitation pump energies is a result of bandgap renormalization with the semiconductor nanowire, which causes longer wavelengths to be preferentially amplified.…”
supporting
confidence: 82%
“…This geometrical arrangement enables the optical characterization of single vertical nanocavities by using a focused beamspot smaller than the distance between adjacent nanowires, as well as high-resolution photoluminescence imaging by UVlaser scanning confocal microscopy Lasing has been observed in ZnO structures including micropillars, nanowires, and nanorods. 3,[7][8][9][10][11] Investigation of the lasing characteristics of high density ZnO nanowire arrays has shown that high quality single-crystalline ZnO nanowires constitute ideal lasing nanocavities, which provide both a gain medium and a resonant cavity due to reflection at the planar endfacets. 12,13 Lasing emission of a single nanowire placed horizontally on a substrate was first demonstrated in 2001 and subsequent work has developed a further understanding of the lasing mechanism in ZnO nanostructures.…”
mentioning
confidence: 99%
“…These peaks correspond to the longitudinal cavity modes that are formed when the propagation losses are compensated by gain, allowing the photonic modes to resonate between the reflective NW end-facets. 33 As the pump intensity approaches the lasing threshold, the emission output exhibits a superlinear increase (Figure 2b), which is expected. At I ex > 0.78 J/cm 2 , the spectrum is dominated by the sharp emission lines with an intensity several orders of magnitude greater than the spontaneous emission background.…”
supporting
confidence: 63%
“…Lastly, the confinement losses (or mode intensity losses) in thin NWs is more significant than in the thick NWs. 33 Therefore, to achieve the lasing in thinner NWs, higher laser pump fluence is needed to compensate for these losses, resulting in higher photogenerated carrier densities. Hence, a larger blue shift of the lasing wavelengths in the thin NWs compared to the thick NWs is therefore expected.…”
mentioning
confidence: 99%
“…More interest in nanotechnology is growing due to the novel properties of nanomaterials and their potentials for applications in many fields. For example, nanowires can be potentially used in nanophotonics, lasers (Zimmler et al, 2008), nanoelectronics (Javey et al, 2007), solar cells (Tsakalakos et al, 2007), resonators (Tanner et al, 2007) and sensors (Fan et al, 2005). They could also be used as catalysts (Haruta et al, 1993), functional coatings, in nanoelectronics (Garnett et al, 2007) and energy storage .…”
Section: Introductionmentioning
confidence: 99%